2006
DOI: 10.3758/bf03193659
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the perception of 3-D shape from dynamic patterns of binocular disparity

Abstract: In two experiments, we investigated the ability of younger and older observers to perceive and discriminate 3-D shape from static and dynamic patterns of binocular disparity. In both experiments, the younger observers' discrimination accuracies were 20% higher than those of the older observers. Despite this quantitative difference, in all other respects the older observers performed similarly to the younger observers. Both age groups were similarly affected by changes in the magnitude of binocular younger obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…The results of Experiment 1 support previous findings of age-related deficits in the stereoscopic perception of 3-D shape (Norman et al, 2000;Norman, Crabtree, et al, 2006), as well as the findings in those studies that have found reductions in stereoacuity with increasing age (Bell, Wolf, & Bernholz, 1972;Brown, Yap, & Fan, 1993;Haegerstrom-Portnoy, Schneck, & Brabyn, 1999;Jani, 1966;Wright & Wormald, 1992). It is interesting to note that whereas all of the studies to date in which the stereoscopic perception of 3-D shape has been evaluated have shown significant effects of age, the studies in which stereoacuity and aging have been evaluated have had mixed and contradictory results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of Experiment 1 support previous findings of age-related deficits in the stereoscopic perception of 3-D shape (Norman et al, 2000;Norman, Crabtree, et al, 2006), as well as the findings in those studies that have found reductions in stereoacuity with increasing age (Bell, Wolf, & Bernholz, 1972;Brown, Yap, & Fan, 1993;Haegerstrom-Portnoy, Schneck, & Brabyn, 1999;Jani, 1966;Wright & Wormald, 1992). It is interesting to note that whereas all of the studies to date in which the stereoscopic perception of 3-D shape has been evaluated have shown significant effects of age, the studies in which stereoacuity and aging have been evaluated have had mixed and contradictory results.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have similarly shown that younger observers' performance is not adversely affected when their retinal illuminance is reduced by neutral density filters to match the lowered retinal illuminance that normally exists for older observers because of lens opacification or senile miosis (see Bennett, Sekuler, & Ozin, 1999, in which little or no effect of reduced retinal illumination for high-noise conditions was shown; see also Elliott, Whitaker, & MacVeigh, 1990;Habak & Faubert, 2000;Norman, Clayton, Shular, & Thompson, 2004;Norman, Crabtree, et al, 2006). The present results and those of the previous studies suggest that the various effects of age that have been obtained are not due to optical factors but, rather, to neurophysiological changes within the visual system.…”
Section: Author Notementioning
confidence: 91%
See 2 more Smart Citations
“…Within the diffusion model, response bias can be implemented in two different ways: as starting point bias, or drift rate bias (Diederich & Busemeyer, 2006; Ratcliff & McKooon, 2008; Voss, Rothermund, & Brandtstädter, 2008). Starting point bias refers to the whether the starting point is equidistant between the two response boundaries, whereas drift rate bias refers to whether the drift rates for signal (which are positive) and those for noise (which are negative) are equidistant from zero.…”
Section: Resultsmentioning
confidence: 99%